Acinetobacter baumannii strain 6.1 16S ribosomal RNA gene, partial sequence - Kamarudin, Kamarul Rahim; Ngah, Nurziana; Tengku Abdul Hamid, Tengku Haziyamin; Darnis, Deny Susanti (2012)

(untitled)
Accession No.: JX286667 - JX286676. Accepted on 10 July 2012 and released on 26 August 2012 by the GenBank, National Center for Biotechnology Information (NCBI), U.S. National Library of Medicine. This is the highlight of the research entitled “Isolation of pigment-producing bacteria from two Malaysian sea cucumber (Echinodermata: Holothuroidea) species” for the year 2011-2013. Corresponding author: Kamarul Rahim Kamarudin.This is the highlight of the research entitled “Isolation of pigment-producing bacteria from two Malaysian sea cucumber (Echinodermata: Holothuroidea) species” for the year 2011-2013.